INOVASI DAN TANTANGAN GURU DALAM MELAKUKAN PEMBELAJARAN SERTA EVALUASI BERBASIS TEKNOLOGI DI SMAN 1 PONTANG - Iip Saripah; Kurniawan, Asep; Rosmilawati, Ila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information technology has transformed teachers’ approaches to conducting learning assessments. The transition from conventional to digital assessment requires teachers to master technological tools and develop innovations to ensure that evaluation processes are effective, accurate, and aligned with students’ learning needs. This study aims to analyze teachers’ innovations in technology-based assessment, identify the challenges they face, and examine the strategies implemented to optimize assessment practices at SMAN 1 Pontang. A descriptive qualitative approach was employed, using interviews, observations, and documentation. The findings reveal that teachers have utilized various digital platforms such as Google Forms, local CBT systems, LMS platforms, and gamification-based applications. Nevertheless, challenges remain, including limited digital competence, infrastructural issues, technical errors, and pedagogical constraints. The school addresses these challenges through continuous training, infrastructure improvement, digital assessment policies, and collaborative teacher practices. The study concludes that technology-based assessment positively impacts the effectiveness of evaluation but requires systemic support and ongoing competency development.